A Rapid Response Study of the Hercules Gas Well Blowout. Issue 38 (23rd September 2014) - Joye, Samantha B.; Montoya, Joseph P.; Murawski, Steven A.; Özgökmen, Tamay M.; Wade, Terry L.; Montuoro, Raffaele; Roberts, Brian J.; Hollander, David J.; Jeffrey, Wade H.; Chanton, Jeffery P.
<x xml:space="preserve">Abstract</x> On 20 April 2010, the Deepwater Horizon drilling rig lost well control while drilling at the Macondo prospect in the Gulf of Mexico. At the time of the Macondo blowout, the academic scientific community was ill prepared to initiate and rapidly conduct the necessary coordinated interdisciplinary studies of the environments around the discharge area.